Medicinal Plants and Zinc: Impact on COVID-19 Pandemic - Zineb Jalal; Meryem Bakour; Badiaa Lyoussi (The Scientific World Journal, 2021)
The world is currently grappling with the coronavirus disease (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The infection can cause fever, a dry cough, fatigue, severe pneumonia, respiratory distress syndrome, and in some cases death. There is currently no effective antiviral SARS-CoV-2 drug. To reduce the number of infections and deaths, it is critical to focus on strengthening immunity. This review aims to conduct a comprehensive search on the previous studies using Google Scholar, ScienceDirect, Medline, PubMed, and Scopus for the collection of research papers based on the role of zinc in the immune system, the antiviral activity of zinc, the effect of zinc supplementation in respiratory infections, the therapeutic approaches against viral infections based on medicinal plants, and the role of plants’ bioactive molecules in fighting viral infections. In conclusion, we highlighted the pivotal role of zinc in antiviral immunity and we suggested the bioactive molecules derived from medicinal plants as a search matrix for the development of anti-SARS-CoV-2 drugs.